The Effect of Family Knowledge, Attitude and Income on Anemia in Adolescents - Saddiyah Rangkuti (Institute of Computer Science (IOCS), 2020)
Effect of knowledge, attitudes and family income on anemia in adolescents. One of the factors that influence the incidence of anemia as shown by Dreyfuss et al. (2000), is vitamin A deficiency. Another factor, namely lack of energy and protein consumption can also reduce hemoglobin levels in the blood (Berger et al., 1997). Research Objectives: To determine the relationship between knowledge of adolescent girls and the incidence of anemia in female high school students in Medan. This study aims to determine the relationship between the attitudes of young women to the incidence of anemia in high school students in Medan. The purpose of this study was to determine the relationship between family income of adolescent girls and the incidence of anemia in female high school students in Medan. The study was conducted for two months starting from March to January 2020. The most dominant variable/the biggest influence on the incidence of anemia, seen from the largest OR value, was the attitude variable (P = 0.000). So that the attitude of young women has a chance of 10.931 times experiencing anemia, after being controlled by the variables of eating habits and menstrual patterns.